Irisin stimulates protective signaling pathways in rat hippocampal neurons - Lourenco, Mychael V.; de Freitas, Guilherme B.; Raony, Ícaro; Ferreira, Sergio T.; De Felice, Fernanda G. (Frontiers in Cellular Neuroscience, 2022)
Physical exercise stimulates neuroprotective pathways, has pro-cognitive actions, and alleviates memory impairment in Alzheimer’s disease (AD). Irisin is an exercise-linked hormone produced by cleavage of fibronectin type III domain containing protein 5 (FNDC5) in skeletal muscle, brain and other tissues. Irisin was recently shown to mediate the brain benefits of exercise in AD mouse models. Here, we sought to obtain insight into the neuroprotective actions of irisin. We demonstrate that adenoviral-mediated expression of irisin promotes extracellular brain derived neurotrophic factor (BDNF) accumulation in hippocampal cultures. We further show that irisin stimulates transient activation of extracellular signal-regulated kinase 1/2 (ERK 1/2), and prevents amyloid-β oligomer-induced oxidative stress in primary hippocampal neurons. Finally, analysis of RNA sequencing (RNAseq) datasets shows a trend of reduction of hippocampal FNDC5 mRNA with aging and tau pathology in humans. Results indicate that irisin activates protective pathways in hippocampal neurons and further support the notion that stimulation of irisin signaling in the brain may be beneficial in AD.